500 handmade books : inspiring interpretations of a timeless form - Tourtillott, Suzanne J. E. (New York : Lark Books, 2008)
Interest in bookbinding and the related arts has exploded in the past decade, inspiring artists to explore the unlimited possibilities of the form. This title showcases a range from the intricacies of an exotic Ethiopian binding with a show-stopping open spine to others that resemble mysterious puzzle boxes
1. Introduction -- 2. The books -- 3. About the juror -- 4. Acknowledgements -- 5. Contributing artists
Includes index
Keywords: Book design